A conserved non-coding element is sufficient but not essential for c-myb expression during zebrafish haematopoiesis - Almulhim, Jawaher (2021)
Haematopoiesis is the process by which all blood cell types form in a vertebrate organism. c-myb is an essential transcription factor that is widely expressed in haematopoietic stem and progenitor cells and is known to induce leukaemia when overexpressed. During normal haematopoiesis, it plays important roles during stem cell formation, self-renewal, maintenance, proliferation and differentiation of HSCs/ progenitors. To gain a deeper insight into the transcriptional regulation of this key transcription factor, it is important to learn more about the cis-regulatory DNA elements that control its expression. Cis-regulatory DNA elements, like promoters and enhancers, are generally less conserved than the corresponding coding sequences. Nevertheless, long-range genomic DNA sequence alignments have identified a conserved non-coding DNA element (CNE1) downstream of the c-myb gene that is remarkably conserved from fish to man. Testing the zebrafish regulatory element (zRE1) containing zebrafish conserved non-coding element (zCNE1) and its mouse equivalent mRE1 in stable transgenic zebrafish lines, named qmc85 and qmc156, has revealed that both are sufficient to direct zebrafish c-myb promoter activity to haematopoietic cells. Both lines display GFP expression in blood cells of the larval caudal haematopoietic tissue and the adult kidney marrow (KM). In this study, single cell RNA-sequencing (scRNA-Seq) was used to determine the gene expression profile and, thereby, the nature of the GFP+ KM cells in the qmc85 line. The scRNA-Seq data revealed that all of the cells expressed lysozyme, a marker for neutrophilic granulocytes. Gene transcripts that are usually associated with other blood cell lineages were not found at significant levels. Instead, the cells expressed numerous additional neutrophil genes at levels that correlated with those of the lysozyme mRNA. Further analysis shows that the neutrophils were at different maturation stages. To investigate whether zRE1 containing zCNE1 and three potential cis-regulatory elements (PEs) are necessary for endogenous c-myb expression, CRISPR/Cas9 technology was used to delete the elements from the zebrafish c-myb locus. Successful deletion of zRE1 alone and in combination with all three PEs yielded the mutant alleles qmc193 and qmc194, respectively. Embryos homozygous for the two mutant alleles did not display an obvious reduction in c-myb expression in blood cells of the CHT, and neither did embryos that were compound heterozygous for either qmc193 or qmc194 and the previously published c-myb null allele t25127. Larvae that are homozygous for qmc193 and qmc194 were viable and could be raised to adulthood. These data suggest that zCNE1, though sufficient to direct c-myb promoter activity to haematopoietic cells (neutrophil lineage) but is not essential for c-myb expression in those cells. Testing the human hRE1 element containing hCNE1 in the stable transgenic line qmc195 revealed that hCNE1 is able to direct transgene expression in embryonic haematopoietic progenitors and in the adult kidney marrow.